Revision of the genus Cestoplectus Lamb (Diptera: Chloropidae) with description of a new species from India - Tilak, Jyothi; Cherian, P.T. (ENTOMON, 2015)
A new species of the rare Oriental genus Cestoplectus Lamb from India is described. This is the fifth species coming under the genus of which three are distributed in India. A key to all the species of the genus and short notes on Indian species are given.